Analysis of Operators Physical and Mental Workload at Thresher Station at PT. Beurata Subur Persada (Bsp) Nagan Raya - Said Al Ahsan; Nissa Prasanti (Jurnal Inotera, 2023)
PT Beurata Subur Persada (BSP) is a company engaged in processing Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO) located in Nagan Raya District, Aceh Province. In carrying out the production process, the thresher station is one of the stations in the factory that functions as a machine that ejects fruit from the stage of the jongkos (palm stalk) by slamming the FFB into the thresher drum successively. However, based on initial observations, it is known that the BSP operator who controls the thresher machine also controls other machines, so this increases the physical and mental workload of the operators. The purpose of this study was to analyze the physical workload and mental workload of station operators using the %CVL method and the NASA-TLX method which are influenced by the subjectivity of the operators. The results of the study found that there were 2 operators who experienced rather high physical workloads, while the other 2 operators experienced moderate physical workloads. While measuring the mental workload it is known that all operators are in the moderate category.